2021
DOI: 10.1519/jpt.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder and Data-Driven Fall Screen in a Program of All-Inclusive Care for the Elderly: Quality Improvement Initiative

Abstract: Background and Purpose: The Program of All-Inclusive Care for the Elderly (PACE) delivers community-based long-term care services to low-income, nursing home eligible adults. In the PACE population, one of the most common reasons for hospitalizations is falls. The purpose of this quality improvement study was to create a stakeholder-driven process for developing a fall risk screen and evaluate how well this process discriminated injurious and noninjurious fallers. Methods: The quality improvement design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The acute care setting accounted for the largest number of included studies ( n = 41, 59%), 27,28,33,34,37,39-42,45,46,48,50,52,53,55,58,59,62,66,68,70-74,76-78,88,89,95-98,100-105 followed by the outpatient setting ( n = 19, 27%). 29-32,36,38,47,49,54,56,60,61,64,67,69,79,80,93,99 Other practice settings included inpatient rehabilitation ( n = 6, 8.6%), 36,43,57,65,75,76 home health ( n = 2, 2.9%), 44,63 other ( n = 2, 2.9%), 19,81 and academia ( n = 2, 2.9%). 35,51 The other category comprises a scoping review by Jesus et al 19 and a study by Steenbruggen et al 81 in which the practice setting was not made clear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The acute care setting accounted for the largest number of included studies ( n = 41, 59%), 27,28,33,34,37,39-42,45,46,48,50,52,53,55,58,59,62,66,68,70-74,76-78,88,89,95-98,100-105 followed by the outpatient setting ( n = 19, 27%). 29-32,36,38,47,49,54,56,60,61,64,67,69,79,80,93,99 Other practice settings included inpatient rehabilitation ( n = 6, 8.6%), 36,43,57,65,75,76 home health ( n = 2, 2.9%), 44,63 other ( n = 2, 2.9%), 19,81 and academia ( n = 2, 2.9%). 35,51 The other category comprises a scoping review by Jesus et al 19 and a study by Steenbruggen et al 81 in which the practice setting was not made clear.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 70 total included studies in this review, 18 (26%) 28,37,39,40,43-45,48,52,60,68,70,73,74,77,79,96,102 were approved by local ethics boards, 19 (27%) 32-34,36,41,46,47,49,50,53,55,56,58,63,64,67,81,97,100 sought approval but were considered exempt, 15 (21%) 19,35,38,42,57,59,61,62,65,71,72,75,78,80,93 reported that seeking approval was not necessary at their institution based on the type of project proposed and current regulations, and 18 (26%) 27,29-31,51,54,66,69,76,88,89,95,98,99,101,103-105 made no mention of ethics oversight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who reported a recent fall were also recruited. The falls risk screen and scoring criteria are described elsewhere 13 . Exclusions included contraindications to high‐intensity exercise, 22 weight‐bearing precautions, neurodegenerative or acute neurological diagnoses (e.g., Parkinson's Disease, stroke, traumatic brain injury), inability to give consent due to cognitive impairment, or residing in long‐term care.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the association between falls and physical function in a PACE population, our research team collaborated with InnovAge PACE in Colorado for two years to collect objective measures of physical function on all participants. From those data, we created a fall screening assessment to stratify fall risk 13 . While falls among PACE participants are multifactorial, our findings demonstrated that a frequent primary or contributing factor is reduced physical function 14–16 .…”
Section: Introductionmentioning
confidence: 98%